Relationship between aggressive behavior, depressed mood, and other disruptive behavior in Puerto Rican children diagnosed with Attention Deficit and Disruptive Behaviors Disorders - Cabiya-Morales, José J.; Padilla, Lymaries; Sayers-Montalvo, Sean; Pedrosa, Orlando; Pérez-Pedrogo, Coralee; Manzano-Mojica, Joel (Puerto Rico Health Sciences Journal, 2007)
Objective: The present study was directed at examining the relationship between aggressive behavior, depressed mood, other disruptive behaviors in children diagnosed with ADHD or ODD disorders in Puerto Rico. Methods: One hundred seventy six (176) students (127 males and 49 females) from 12 public elementary schools in the San Juan Area of Puerto Rico participated in the study. The participants were divided into a group of ADHD children who exhibited aggressive behavior, a group of ADHD children that did not show aggressive behavior, and a normal group. Several self-report measures were administered to the children and teachers. Results: Our results indicate that the best predictor of aggressive behavior was the hyperactivity and impulsiveness for both ADHD males and females. In addition, depressed mood in both males and females was also a significant predictor of aggressive behavior in Puerto Rican ADHD children. However, in females the social problems variable was also found to be a significant grouping variable. Conclusion: The first conclusion of these results is that inattentiveness does not appear to be a relevant factor in ADHD Puerto Rican children who exhibit aggressive behavior. Second, we need to be cognizant to the fact that Puerto Rican ADHD children do exhibit high co-morbidity for aggressive behavior, depressed mood, and social problems. Thus, our diagnostic and treatment approaches with ADHD Puerto Rican children need to include an assessment of the social environment of the child and its effect on his emotional state, in particular his or her mood.